KONTROVERSI PERKAWINAN BEDA AGAMA: Status Hukum Antara Status Hak Sipil dan Batasan Legal dalam Putusan Pengadilan - Ni'matul Fauziah (PT Taskuliah Edukasi Indonesia, 2025)
This article discusses the controversy surrounding interfaith marriages that occurred in the Jakarta District Court in Case No. 131/Pdt.P/2021/Pn.Jkt.Sel. The existence of justice is disrupted because there are conflicting opinions from the Supreme Court's jurisprudence regarding Islamic family law, namely, interfaith marriages. There is no clarity in the regulations of the Marriage Law regarding interfaith marriages, leading to conflicts between religious norms and the absence of clear legal provisions, as well as some ambiguous interpretations. On November 7, 2020, the marriage between Cakra Dharma (Islam) and Bernadeth Sylvanny Pramesya H. (Catholic) sparked public controversy, as the decision of the South Jakarta District Court was subsequently made. This research is a literature study, using a legal-normative approach and case studies. The data used in this study are derived from secondary sources, including primary legal materials, secondary legal materials, and tertiary legal materials. The data were analysed qualitatively and through legal normative analysis to obtain results and conclusions. The result of the research is the granting of permission to be registered at the civil registry office. The applicant has already conducted an interfaith marriage, incorporating both Catholic and Islamic religious practices, and then reported it to the court. The ongoing debate highlights the need for a balanced approach that respects religious norms and individual freedom. The South Jakarta District Court justified its decision on the interfaith marriage case by navigating legal gaps, historical judicial interpretations, Supreme Court guidelines, and the influence of religious law. The ruling reflects the complex interplay between upholding religious norms and addressing human rights issues within the framework of Indonesian law. Contribution: This study contributes to the understanding of the role of the courts in responding to the legal vacuum surrounding interfaith marriages and its impact on legal practice and policy in Indonesia. [Artikel ini membahasa tentang kontraversi pernikahan beda agama yang terjadi di pengadilan negeri Jakarta dalam Penetapan Perkara Nomor 131/Pdt.P/2021/Pn.Jkt.Sel. Eksistensi keadilan terganggu karena terdapat pendapat kontra dari yurisprudensi hakim MA mengenai hukum keluarga Islam, yaitu perkawinan beda agama. Belum ada kejelasan peraturan dalam Undang-Undang Perkawinan yang membahas perkawinan beda agama, sehingga timbul pertentangan norma agama atas ketiadaan hukum dan beberapa penafsiran tidak jelas. Pada tanggal 7 November 2020 pernikahan antara Cakra Dharma (Islam) dengan Bernadeth Sylvanny Pramesya H. (Katolik) timbul kontroversi masyarakat dalam penetapan hakim Pengadilan Negeri Jakarta Selatan. Jenis penelitian ini adalah studi pustaka, menggunakan pendekatan yuridis-normative dan studi kasus. Data yang digunakan dalam penelitian ini bersumber dari data sekunder, yang mencakup bahan hukum primer, bahan hukum sekunder, dan bahan hukum tersier. Dan data dianalisis secara kualitatif dan hukum normative untuk mendapatkan hasil dan kesimpulan. Hasil penelitian yaitu pemberian izin untuk dicatatkan di kantor catatan sipil. Pemohon sudah melaksanakan perkawinan beda agama dalam proses menurut iman Katolik dan syariat Islam, kemudian melaporkan ke pengadilan. Perdebatan yang sedang berlangsung menyoroti perlunya pendekatan yang seimbang yang menghormati norma-norma agama dan kebebasan individu. Pengadilan Negeri Jakarta Selatan menjustifikasi keputusannya atas kasus pernikahan beda agama dengan menavigasi kekosongan hukum, interpretasi yudisial historis, arahan Mahkamah Agung, dan pengaruh hukum agama. Putusan tersebut mencerminkan interaksi yang kompleks antara menegakkan norma-norma agama dan menangani masalah hak asasi manusia dalam kerangka hukum Indonesia. Kontribusi: Penelitian ini berkotrinusi terhadap peran pengadilan dalam merespons kekosongan hukum perkawinan beda agama serta dampaknya terhadap praktik hukum dan kebijakan di Indonesia].